Comparison of Ultrasound-Microwave-Assisted and Hot Reflux Extractions of Polysaccharides from Alpinia officinarum Hance: Optimization, Characterization, and Antioxidant Activity - Haibao Tang; Baogang Zhou; Mengge Sun; Yihan Wang; Ran Cheng; Tao Tan; Dongsheng Yang (Molecules)
Alpinia officinarum Hance exhibits various bioactivities, with polysaccharides being one of its key bioactive components. However, the relationship between the structural characteristics of these polysaccharides and their bioactivities remains unclear and underexplored. In this study, to optimize the extraction process, a Response Surface Methodology-based design combined with single-factor experiments was applied to determine the optimal conditions for the ultrasonic-microwave-assisted extraction of polysaccharides from A. officinarum. The primary structural characteristics and antioxidant activities of two polysaccharide fractions, PAOR-1 extracted by ultrasonic-microwave-assisted extraction and PAOR-2 extracted by hot reflux extraction (HRE), were systematically compared. The optimal extraction conditions, including a liquid–solid ratio of 1:50, extraction time of 19 mins, and ultrasonic power of 410 W, yielded a maximum polysaccharide extraction rate of 18.28% ± 2.23%. The extracted polysaccharides were characterized as acidic polysaccharides with a three-dimensional structure. PAOR-1 and PAOR-2 have different monosaccharide compositions, surface morphologies, and thermal stabilities. The antioxidant activity in vitro studies suggest that PAOR-1 may have higher antioxidant activity than PAOR-2 due to its higher content of uronic acids, lower relative molecular mass, and a more closely packed spatial configuration. These findings provide a theoretical basis for the development and utilization of AOR.